Perlindungan Hukum terhadap Anak Korban Tindak Pidana Pencabulan di Lingkungan Keluarga - I Gede Susila Putra; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
Child sexual immorality is a social problem that is very disturbing to society. This sexual abuse of children needs very serious attention from all circles. imposing criminal sanctions on perpetrators of criminal acts of sexual immorality certainly cannot be separated from the role of judges, prosecutors, and the police as law enforcement officers in order to achieve peace in people's lives. There are also problem formulations (I) How is the legal protection for child victims of sexual immorality? (2) What are the sanctions for perpetrators of sexual abuse against children? This study uses the normative method because there are still vague norms, based on the opinions of law and law scholars. According to Decision Number 978 I Pid.Sus I 2016 I PN Ops, punishment for perpetrators of child molestation is regulated in Article 760 in conjunction with Article 81 Paragraph 3 of Law Number 35 Year 2014 concerning Amendments to Law Number 23 Year 2002 Concerning Child Protection which reads